1989
DOI: 10.1037/0022-006x.57.1.76
|View full text |Cite
|
Sign up to set email alerts
|

Differences between more and less effective psychotherapists: A study of select therapist variables.

Abstract: This study examined differences between more and less effective trainee psychotherapists. Therapists were assigned to one of two groups depending on whether the preponderance of their patients' changes in symptomatology indicated more or less improvement over the course of therapy. Therapist variables included emotional adjustment, relationship skills, eliciting patient involvement, credibility, directiveness, and theoretical orientation. Less effective therapists were revealed to have lower levels of empathic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
109
1
3

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(119 citation statements)
references
References 70 publications
3
109
1
3
Order By: Relevance
“…For example, there are indications that therapists or encounter-group leaders who are charismatic yet highly confrontational and intrusive can place clients at risk for deterioration (Mohr, 1995;Yalom & Lieberman, 1971). Perhaps not surprisingly, low levels of therapist empathy and warmth, whether rated by clients or therapists themselves, are predictive of client deterioration (Lafferty, Beutler, & Crago, 1989;Mohr, 1995). As some authors have observed, the identification of potentially harmful therapists may ultimately prove to be even more important than the identification of potentially harmful therapies (C. Boisvert, personal communication, February 2006).…”
Section: Therapist Variablesmentioning
confidence: 99%
“…For example, there are indications that therapists or encounter-group leaders who are charismatic yet highly confrontational and intrusive can place clients at risk for deterioration (Mohr, 1995;Yalom & Lieberman, 1971). Perhaps not surprisingly, low levels of therapist empathy and warmth, whether rated by clients or therapists themselves, are predictive of client deterioration (Lafferty, Beutler, & Crago, 1989;Mohr, 1995). As some authors have observed, the identification of potentially harmful therapists may ultimately prove to be even more important than the identification of potentially harmful therapies (C. Boisvert, personal communication, February 2006).…”
Section: Therapist Variablesmentioning
confidence: 99%
“…While there is agreement that coaches must be seen as credible to be effective (Joo, 2005;Judge & Cowell, 1997;Passmore & Fillery-Travis, 2011;Segers et al, 2011;Sue-Chan & Latham, 2004), there is debate around how this credibility can be established. This debate has been between those who believe that coaches do not need skills or expertise in the management or organisation sector in which they work but rather need skills in counselling psychology or therapy (Ajzen, 1992;Beutler, Machado, & Neufeldt, 1994;Lafferty, Beutler, & Crago, 1989;Petty & Cacioppo, 1984), and those who argue that coaches must have skills or expertise in either executive management development and/or in the sector in which they are practising (Berglas, 2002;Eggers & Clark, 2000;Evers et al, 2006;Hagen, 2010;Joo, 2005;Passmore & Fillery-Travis, 2011;Smither et al, 2003;VanFleet, 1999). The evidence available in the 111 studies reviewed here tends towards the latter conclusion, that skills or expertise in the sector or in executive management are preferable (De Haan, 2008a;Judge & Cowell, 1997;Kiel et al, 1996;Orenstein, 2006;Smith Glasgow et al, 2009;Wasylyshyn, 2003).…”
Section: Research Question 4: Understanding Coach Credibilitymentioning
confidence: 99%
“…First, we examined therapists' feelings of empathy toward racially diverse clients. Empathy is a foundational disposition in counseling (Bohort, Elliot, Greenberg, & Watson, 2002) and has been found to be one of the most important factors in discriminating effectiveness in therapy (Bohort et al, 2002;Lafferty, Beutler, & Crago, 1989). Empathy is also considered essential to cross-cultural counseling (Ho, 1992;Ridley & Lingle, 1996).…”
mentioning
confidence: 99%